2017
DOI: 10.1155/2017/4396870
|View full text |Cite
|
Sign up to set email alerts
|

Total Parenteral Nutrition Successfully Treating Black Esophagus Secondary to Hypovolemic Shock

Abstract: We present a patient who developed black esophagus secondary to hypovolemic shock and was placed on total parenteral nutrition for three weeks after hospital discharge. The area of interest is the multimodal approach used in treatment of this noncompliant patient. Even with a high mortality rate, this case illustrates a successful outcome of a patient who responded to appropriate immediate therapy resulting in complete resolution of the necrosis with no further development of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…Of these cases, we managed to extract data from 79 articles having 105 cases of AON (online supplementary table 1). 5–82 Data could not be extracted from (n=13) of the articles containing a total of (n=20) cases 4 83–95. The most common reasons for these were unavailability of complete data or the language being other than English.…”
Section: Discussionmentioning
confidence: 99%
“…Of these cases, we managed to extract data from 79 articles having 105 cases of AON (online supplementary table 1). 5–82 Data could not be extracted from (n=13) of the articles containing a total of (n=20) cases 4 83–95. The most common reasons for these were unavailability of complete data or the language being other than English.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] These case studies suggested low systemic perfusion due to alcoholic lactic acidosis, hypothermia, and impaired mucosal defence are major pathological causes of alcohol-induced AEN. [8][9][10][11][12][13][14][15][16] Multiple forensic studies on alcohol-induced AEN have shown hemorrhagic shock resulting from esophageal necrosis is the most common cause of death, followed by cardiac arrest and hypothermia (table 2). [17][18][19][20][21] On autopsy, a black pigmentation involving the distal esophagus with or without Wischnewski lesions (red brownish erosions of the mucosa) and hemorrhagic fluid collection are commonly reported findings related to alcohol-induced AEN (table 2).…”
Section: Pathogenesis and Etiologymentioning
confidence: 94%
“…AEN associated with active alcohol drinking is a rare entity, and only nine cases have been reported in the current literature (table 1). [8][9][10][11][12][13][14][15][16] Upper gastrointestinal hemorrhage, vomiting, abdominal pain and unresponsiveness are common presenting symptoms in these cases with AEN associated with drinking alcohol ranging 2-8 pints daily. [8][9][10][11][12][13][14][15][16] These case studies suggested low systemic perfusion due to alcoholic lactic acidosis, hypothermia, and impaired mucosal defence are major pathological causes of alcohol-induced AEN.…”
Section: Pathogenesis and Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Acute esophageal necrosis (AEN), also known as Gurvits syndrome or black esophagus, is a particularly rare syndrome with an incidence of only 0.1-0.28% and a 4:1 predilection to males [ 1 ]. It has a striking endoscopic appearance and is notable for nearly universal involvement of the distal esophagus with various proximal extensions of black necrotic appearing mucosa and abrupt interruption at the gastroesophageal junctions (GEJ) [ 2 ]. The degree of tissue penetration is variable and likely related to the severity of the insult [ 3 - 4 ].…”
Section: Introductionmentioning
confidence: 99%